Peningkatan HOTS Mahasiswa dengan Pendekatan Etnopedagogi pada Mata Kuliah Pembelajaran Sastra - Afrodita, Meli; Wulandari, Catur; Agustina, Emi (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to improve students' Higher Order Thinking Skills (HOTS) in the Literature Learning course through the application of an ethnopedagogical approach. This study uses a classroom action research (CAR) design implemented in two cycles. Each cycle consists of four stages: planning, action, observation, and reflection. Data were obtained through tests, observations, interviews, and documentation. The results showed a significant increase in students' HOTS skills after the application of ethnopedagogy. The average score in cycle I was 76.26 (B+) with a completion rate of 32.35%, increasing in cycle II to 81.57 (A-) with a completion rate of 85.29%. Students were better able to analyze cultural values, conduct reflective evaluations, and produce more original, local culture-based creative works. This study concludes that the ethnopedagogical approach is effective in strengthening higher order thinking skills through contextual and culture-based literature learning.  Keywords: ethnopedagogy; HOTS; literature learning